Efeitos de uma desintegrina RGD recombinante na migração de uma linhagem celular de carcinoma de células escamosas de origem oral - Montenegro, Cyntia de Freitas (2016)
Cancer is a group of diseases related to abnormal cell growth and ability to invade tissues. These skills result in the development of metastases, leading to death in many of the patients. During the process of invasion, the cells find a connective tissue rich in fibronectin and collagen in which they will have to go through in order to reach the blood vessels and then the metastatic site. Fibronectin adhesion receptors such as αvβ3 and α5β1 integrins are essential for cells to be able to move through the fibronectin fibers. Integrins bind to the extracellular matrix (ECM) proteins via the RGD motif present in fibronectin, making these cell types migration receptors a potential target for the study of cancer. Thus, the effect of DisBa-01, an RGD containing motif disintegrin, was investigated in two cell specialized on migration; fibroblasts (BJ) and oral squamous cell carcinoma (SCC25). DisBa-01 (1 and 2 μM) was able to reduce cancer cells migration speed and directionality, but not fibroblasts, on time-lapse experiments performed on fibronectin coated plates. In order to understand if the effect of DisBa-01 is associated with alterations in cellular adhesion, cells were plated on fibronectin and stained with anti-paxillin. Images acquired by confocal microscopy show changes in focal adhesions, which have become larger and more numerous. These data were confirmed, by time-lapse assays using Total Internal Reflection Fluorescence (TIRF) in cells transfected with paxillin. The expression of key fibronectin receptors, α5, β3 and αv is present similarly in both strains, while the β1 subunit is expressed in lower amounts in OSCC cells. To investigate the probable relationship of migration inhibition with integrin β3 level, this subunit was overexpressed in the OSCC cells and all parameters analyzed were restored. Taken together, these results demonstrate the ability of DisBa-01 to affect cell migration depending on integrin expression level and by modulating the dynamics of cell adhesions.